1980
DOI: 10.2131/jts.5.91
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Raw and Extracted-Aged Garlic Juice on Growth of Young Rats and Their Organs After Peroral Administration

Abstract: The effects of peroral administration of raw garlic juice and extracted-aged garlic juice (garlic extract) were studied with female Wistar strain rats. For the examination, 5, 5 and 10 rats were sacrificed after 3, 8 and 21 days respectively. In the group to which raw garlic juice (5 ml/kg) was administered 5 rats died of the serious stomach injury in 21 days and body weight of still living rats was down at the beginning as food and water intake were decreased. The growth of rats to which raw garlic juice admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 94 publications
(54 citation statements)
references
References 3 publications
3
49
0
Order By: Relevance
“…Some studies have suggested that normal cells were more resistant to apoptosis induction by OSCs compared with cancer cells [Karmakar et al, 2007;Kim et al, 2007;], however, the mechanism of this selectivity remains unknown. On the other hand, other studies have demonstrated toxicity of higher doses of fresh garlic extract in normal cells of the gastrointestinal tract [Nakagawa et al, 1980;Joseph et al, 1989]. Our unpublished studies on Swiss mice also suggested toxicity of higher doses of DATS (62 mg per kg of body weight) causing death of animals.…”
Section: Anticancer Effect Of Garlic and Garlic-derived Compounds In supporting
confidence: 49%
See 1 more Smart Citation
“…Some studies have suggested that normal cells were more resistant to apoptosis induction by OSCs compared with cancer cells [Karmakar et al, 2007;Kim et al, 2007;], however, the mechanism of this selectivity remains unknown. On the other hand, other studies have demonstrated toxicity of higher doses of fresh garlic extract in normal cells of the gastrointestinal tract [Nakagawa et al, 1980;Joseph et al, 1989]. Our unpublished studies on Swiss mice also suggested toxicity of higher doses of DATS (62 mg per kg of body weight) causing death of animals.…”
Section: Anticancer Effect Of Garlic and Garlic-derived Compounds In supporting
confidence: 49%
“…Indeed, apart from antioxidant effects of AGE and some others garlic compounds, there are a few reports highlighting the toxic effects of garlic. Nakagawa reported that raw garlic juice at a high dose (5 ml/kg of body weight) led to death of rats due to stomach injury [Nakagawa et al, 1980]. Another study demonstrated that the administration of aqueous raw garlic extract in drinking water significantly elevated aspartate aminotransferase level, suggesting liver injury [Joseph et al, 1989].…”
Section: Antioxidant Effects Of Garlic and Aged Garlic Extractmentioning
confidence: 99%
“…In brief, sliced garlic is soaked with aqueous alcohol and extracted over 10 months at room temperature. As the result, AGE is less irritating and toxic [4,5], and has many beneficial pharmacological properties [6][7][8][9][10][11]. AGE contains not less than 0.05% of S-allyl-L-cysteine (SAC) calculated on the dried basis [12,13].…”
Section: Garlicmentioning
confidence: 99%
“…[2][3][4] However, it is not practical to use raw garlic because it has various side effects such as anemia, weight loss, growth reduction, and decrease of caecal microflora and serum protein. 5,6) Aged garlic extract (AGE), which is extracted for more than 10 months, is less irritating and toxic. 5,7) A large number of pharmacological studies have demonstrated that AGE possesses anti-oxidative, [8][9][10] anti-stress, 11) immunomodulating, 12) cardiovascular 13,14) and hepatoprotective 15,16) properties.…”
mentioning
confidence: 99%
“…5,6) Aged garlic extract (AGE), which is extracted for more than 10 months, is less irritating and toxic. 5,7) A large number of pharmacological studies have demonstrated that AGE possesses anti-oxidative, [8][9][10] anti-stress, 11) immunomodulating, 12) cardiovascular 13,14) and hepatoprotective 15,16) properties. Moreover, AGE has been shown to be superior to raw garlic in terms of its anti-oxidation properties, and amelioration of physiological and psychological stress.…”
mentioning
confidence: 99%